Fatal Fulminant Hepatic Failure from Adenovirus in Allogeneic Bone Marrow Transplant Patients. (15th August 2012) - Vyas, Jatin M.; Marasco, Wayne A.
Abstract : We report two cases of fatal hepatic failure in patients who received matched unrelated bone marrow transplantation. Both patients presented with high fevers, abnormal liver functions tests, and hypodense lesions in the liver by CT scan. Histologic examination of postmortem liver samples demonstrated extensive necrosis, and immunohistochemistry was positive for adenovirus.